2017
DOI: 10.1007/s13346-016-0354-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel route of insulin delivery using an implant-mediated drug delivery system

Abstract: Patients with diabetes mellitus (DM) frequently require multiple painful injections of insulin to manage their blood glucose level. A newly introduced, modified titanium implant, the implant-mediated drug delivery system (IMDDS), has the advantage of sustained, needle-free drug delivery. We evaluated the feasibility of the IMDDS as an alternative route of insulin delivery in an alloxan-induced rabbit DM model. Among a total of 30 rabbits with IMDDSs, 25 survived the induction and had a blood glucose level (BGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…80 Their shrink-swell activity works either as a sensor or as an insulin releasing agent. 81 A polymerised lectin gel is the basis of an in vivo peritoneal system by Taylor in which insulin output is controlled by a variable viscosity gel from an implantable and refillable reservoir (Figure 16) and extends the insulin implant concept 82,83 to closed loop. 43,[84][85][86][87]…”
Section: Release Mechanism: 2 -Bolusmentioning
confidence: 99%
“…80 Their shrink-swell activity works either as a sensor or as an insulin releasing agent. 81 A polymerised lectin gel is the basis of an in vivo peritoneal system by Taylor in which insulin output is controlled by a variable viscosity gel from an implantable and refillable reservoir (Figure 16) and extends the insulin implant concept 82,83 to closed loop. 43,[84][85][86][87]…”
Section: Release Mechanism: 2 -Bolusmentioning
confidence: 99%
“…Moreover, local or systematic use of insulin could improve implant osseointegration in osteoporotic and diabetic rats [ 43 , 44 ]. The dental implants could even serve as a novel route of insulin delivery by an implant-mediated drug delivery system [ 45 ]. Another study has shown that insulin could promote angiogenesis [ 46 ], which is also a conducive factor to early osseointegration.…”
Section: Discussionmentioning
confidence: 99%
“…The parenteral route of administration, such as intramuscular, subcutaneous, and intravenous, have various superiority over the gastrointestinal manner, which is the most acceptable, economical, and suitable. These types of administration prepare high bioavailability, the rapid activity of drugs, and often continuous usage of intravenous injection [ 75 ]. In addition, TiO 2 diamond-shaped nanoparticles are functionally loaded with doxorubicin and PEG chains.…”
Section: Methodsmentioning
confidence: 99%